Al-Mughtaribun: American Law and the Transformation of Muslim Life in the U.S. by Kathleen Moore. New York: SUNY Press, 1995, 211 pp. (American Journal of Islam and Society, 1997)
The focus of this book is on "the gradual transformation of American Muslims'perceptions and self-identification, coaxed by the ways American civillaw has penetrated and come to dominate their daily lives" (p. vii). Hence, thebook attempts to show the link between law and society by using Muslims inthe United States as a case study. It is of interest to sociologists, legal historians,political scientists, and scholars of religion and touches on the themes ofcivil rights, freedom of religion, social change, the status of minorities, andassimilation.Moore shows how Muslims in the United States have been affected byAmerican immigration law (chapters 2 and 3), religious liberty laws affectingMuslims in prison (chapter 4), hate crime legislation affecting mosques (chapter5), and zoning laws that affect mosques (chapter 6). The sources Mooreuses are historical: court records, interviews, magazine articles, and newspaperstories. She points out that there has been a great transformation in theAmerican legal system's attitude toward Islam. In 1811, the New YorkSupreme Court ruled (in People vs. Ruggles) that the "religion of Mohammed"is an impostor religion, a superstition, and is equally false and unknown(p. x). ln 1962, on the other hand, the District of Columbia U.S. District Courtruled (in Fulwood vs. Clemmer) that Muslims believe in Allah as a supremebeing and as the one true god. It follows, therefore, that the Muslim faith is areligion {p. 82).Have American legal institutions been responsive to the Muslim community?Has the American legal setting transformed the Muslim community? Theanswer to the first question, according to Moore, is that in the 1800s, "No"; butgradually the courts have become more responsive and continue to be moreresponsive as time passes and as Muslims become more politically active. Theanswer to the second question is "Yes."How has the American legal setting transformed the Muslim community?It has limited the numbers of Muslims in the United States (through immigrationrestrictions). It has increasingly allowed Muslims in prison to pray jum'ah,wear kufis on their heads, eat nonpork foods, and obtain copies of the Qur'an.It has protected Muslim mosques from vandalism through stiffer penalties forpeople committing such a crime. It has also restricted the establishment of ...